Methods of teaching essay writing for senior pupils in the Kazakh language - Burkitbayeva, Meruyert; Issayeva, Zhazira; Dauletbekova, Zhanat; Yergubekova, Zhanat; Magzhan, Saule (Opción, 2019)
The article aims to investigate methods of teaching essay writing for senior pupils in the Kazakh language via the qualitative analysis of various models of organizing educational activities. As a result, students of 11-14 years of age should be given descriptions and make an emotional element in them in a very limited amount. In conclusion, the systematic implementation of the selected didactic principles, as practical training shows, ensures the high quality of attribution of essayistic activity in teaching.